Ethnic and Regional Disparities in Self-Reported Smoking Cessation Success: A Cross-Sectional Analysis of Local Authority-Level Data in England - Ferozkhan Jadhakhan; Basiru Gai; Sharanya Sunil Kumar (Healthcare, 2026)
Background/Objectives: Smoking is the leading cause of preventable mortality in England, and NHS Stop Smoking Services (SSSs) routinely report quit outcomes using six aggregated ethnicity categories. These broad categories may obscure meaningful within-category variation. This study examined the regional distribution of English Local Authorities (LAs) and assessed ethnic disparities in self-reported quit-success at LA level. Methods: A cross-sectional ecological analysis was conducted using routinely published SSS data (April 2025–December 2025) for 162 English LAs. One-way ANOVA was conducted across aggregated ethnic categories. Paired-sample t-tests compared mean quit success between the White and Asian or Asian British categories. A Kruskal–Wallis test assessed differences across all six categories, followed by Mann–Whitney U post hoc tests with Bonferroni correction for the three comparisons performed (adjusted α = 0.017). Correlation analysis examined the relationship between quit-date setting and quit success. Results: London contained the largest proportion of Local Authorities (15.6%). After Bonferroni correction (α = 0.0083), none of the within-category comparisons were statistically significant. White and Asian or Asian British categories displayed highly correlated quit success rates (r = 0.708, p < 0.001) with no significant mean difference (t(110) = 0.99, p = 0.324). The Kruskal–Wallis test identified an overall difference across the six aggregated categories (H(5) = 21.67, p < 0.001), largely influenced by the low ranking of the Not Stated group. Quit-date setting and quit success were not meaningfully associated (r = 0.005, p = 0.883).